Cytopathological Diagnosis of an Unusual Cause of Malignant Hydrocele - Jain, Ankur (Clin Med Insights Pathol, 2016)
Testicular involvement in a case of acute lymphoblastic leukemia (ALL) is well reported, but occurrence of “isolated” malignant hydrocele is extremely uncommon. We herein report a case of a 22-year-old man who presented to our hematology clinic with fever and easy fatiguability of 2 weeks’ duration. Examination revealed pallor, cervical lymphadenopathy, and bilateral scrotal swellings. He was diagnosed as a case of Philadelphia-positive ALL (B-cell type) based on peripheral smear, bone marrow examination, and flow cytometry of the marrow aspirate. Ultrasonography of scrotum revealed bilateral hydrocele with normal testes. Cytopathological analysis of the hydrocele fluid showed the presence of lymphoblasts. The patient was treated with modified BFM-90 protocol along with imatinib mesylate (600 mg/day). He achieved complete remission with a minimal residual disease of <0.001% at the end of induction therapy. However, the hydrocele persisted and a repeat cytological examination of the aspirate did not reveal any lymphoblasts. The patient was treated with consolidation (high-dose methotrexate), bilateral testicular irradiation, and re-induction following which the hydrocele disappeared. The patient is currently on maintenance phase of BFM-90 protocol and is alive at one year of follow-up. Contiguous spread from the subclinical testicular involvement is hypothesized as the mechanism for development of hydrocele in the current case. The role of cytopathology in the early diagnosis of testicular involvement in ALL is emphasized here.